2023
DOI: 10.3390/toxins15080495
|View full text |Cite
|
Sign up to set email alerts
|

Alternaria Mycotoxins Analysis and Exposure Investigation in Ruminant Feeds

Abstract: Alternaria mycotoxins are a class of important, agriculture-related hazardous materials, and their contamination in ruminant feeds and products might bring severe toxic effects to animals and even human beings. To control these hazardous compounds, a reliable and sensitive LC-MS/MS (liquid chromatography–tandem mass spectrometry) method was established for simultaneous determination of six target Alternaria mycotoxins in ruminant feeds, including ALT (Altenuene), AME (Alternariol Monomethyl Ether), AOH (Altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Analysis of ZEN in about half a million grains and nuts in large studies by the European Food Safety Agency and around the world showed actual contamination rates between 60% and 80% [10]. ZEN pollution levels are well above the EU and Codex Alimentarius Commission limits [11]. Then, mycotoxins were studied in our feed samples between 2017 and 2021.…”
Section: Introductionmentioning
confidence: 94%
“…Analysis of ZEN in about half a million grains and nuts in large studies by the European Food Safety Agency and around the world showed actual contamination rates between 60% and 80% [10]. ZEN pollution levels are well above the EU and Codex Alimentarius Commission limits [11]. Then, mycotoxins were studied in our feed samples between 2017 and 2021.…”
Section: Introductionmentioning
confidence: 94%